The Best Lies : a novel - Ellis, David, 1967- (New York : G.P. Putnam's Sons, 2024)
"Leo Balanoff is a diagnosed pathological liar with unthinkable skeletons in his family's closet. He's also a crusading attorney who seeks justice at all costs. When a ruthless drug dealer is found dead and Leo's fingerprints show up on the murder weapon, no one believes a word he says. But he might be the FBI's only shot at taking down the dealer's brutal syndicate. Risk his life going undercover for the Feds or head straight to prison for murder? Leo accepts the FBI's offer - but it comes with a price, including a collision course with his ex, Andi Piotrowski, a former cop and "the one who got away." Forced to walk a tightrope between an ambitious FBI agent and a cruel, calculating crime boss, Leo's trapped in a corner. But he has more secrets than anyone realizes, and a few more cards left to play ..."--.
new book 2024 summer.
Keywords: Drug dealers; Investigations; Secrecy; Lawyers; Family secrets; Murder; Mythomania; Undercover operations; Novels; Thriller fiction